Att undervisa i fritidshem: omsorg, lärande och utveckling i en helhet - Lager, Karin (Educare, 2018)
The aim of this article is to explore teaching in a leisure-time centre based on teaching as an entity of care, learning and development. Reforms that characterized Swedish educational systems since the 1980s have in many ways changed the leisure-time centre; and, in The Education Act and the national curriculum, a shift from care to education can be noticed. A revised task for the leisure-time center lifts concepts such as teaching and achievement in line with the primary school's task. The article focuses on a policy process where a specific activity is planned, implemented, documented, evaluated and followed up by teachers in the leisure-time center. The enactment of teaching is analyzed through policy enactment theory, and data is generated by ethnographical method in a case study in a leisure-time centre. The result shows an entity of care, learning and development when teaching focuses on play and development of social and relational abilities, in line with the leisure-time center's task.